Intratumoral Bleeding in a Vestibular Schwannoma - Braga, Emanuelle Rieger; Köhler, Luiza; de Cesaro, Marcelo; Barreto, Tasso; Giacomelli, Richard; Azambuja Jr, Nério Dutra; Varela, Daniel Lima; Mesquita Filho, Paulo Moacir (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Vestibular schwannomas (VSs) account for ∼ 70% of all tumors of the cerebellopontine angle (CPA). Their clinical presentation is often insidious, with progressive hearing loss and involvement of other cranial nerves. Spontaneous hemorrhage in those tumors is very unusual, and generally presents with acute clinical features such as nausea, vomiting, headache and altered consciousness, usually with marked dysfunction of the cranial nerve involved, and with new deficits of neighboring cranial nerves. Asymptomatic patients are extremely rare. We present a case report of an incidental VS with asymptomatic bleeding, which evolved to death after surgery.
Keywords: vestibular schwannoma; vestibular neuroma; intratumoral bleeding; cerebellopontine angle tumors